Burnout in nurses working in China: A national questionnaire survey. Issue 6 (17th December 2020) - Zhang, Wenyu; Miao, Ran; Tang, Jingping; Su, Qingqing; Aung, Lynn Htet Htet; Pi, Hongying; Sai, Xiaoyong
Abstract: Aim: This study aimed to assess the overall status of burnout in nurses in China on a national scale and investigate the demographic characteristics related to burnout and the relationships between demographics, job satisfaction and burnout. Methods: This was a national cross‐sectional study conducted by the Chinese Nursing Association between July 2016 and July 2017. Data were collected using a structured, self‐administered questionnaire. Results: A total of 51 406 registered nurses in 311 Chinese cities completed the questionnaire. Fifty per cent of the participants suffered burnout, and 33.8% of nurses had high scores on emotional exhaustion, 66.6% had high scores on depersonalization and 93.5% had low scores on personal accomplishment; 16.2% reported a high level of job satisfaction, only 0.4% was satisfied with their jobs and 70.7% intended to leave their jobs. Marital status, educational level, income and years of working experience affected job burnout. Nurses with a high level of burnout were more likely to have a high degree of job dissatisfaction and intend to leave their jobs. Conclusion: We found a high prevalence of burnout among nurses in China. Nursing managers need to pay more attention to job burnout and its influencing factors. Interventions to reduce nurse burnout should be implemented. SUMMARY STATEMENT: What is already known about this topic? Burnout is a prolonged response to chronic job‐related stress and it has a negative effect on job satisfaction and quality of nursing care. What this paper adds? The prevalence of burnout among nurses working in China is high. Marital status, educational level, income and years of working experience affect job burnout. Nurses with a high level of burnout have high job dissatisfaction and intend to leave. The implications of this paper: Nursing supervisors and managers need to be more aware of the high prevalence of job burnout among nurses in China. Interventions should be undertaken to prevent or reduce nurse burnout.